Monitoring of active volcanoes in Peru by the Instituto Geofísico del Perú: Early warning systems, communication, and information dissemination - Machacca, Roger (2021)
Volcano monitoring in Peru is carried out by the Instituto Geofísico del Perú (IGP), through its Centro Vulcanológico Nacional (CENVUL). CENVUL monitors 12 out of 16 volcanoes considered as historically active and potentially active in southern Peru and issues periodic bulletins about the volcanic activity and, depending on the alert-level of each volcano, also issues alerts and warnings of volcanic unrest, ash dispersion, and the occurrence of lahars. The information generated by CENVUL is disseminated to the civil authorities and the public through different information media (newsletters, e-mail, website, social media, mobile app, etc.). The IGP volcanology team was formed after the eruption of Sabancaya volcano in 1988. Since then, geophysical and geological studies, volcanic hazards assessments, and multidisciplinary monitoring realized by the IGP, have provided a comprehensive understanding of volcanic activity in Peru and forecast future eruptive scenarios. Currently, 80% of the historically active and potentially active volcanoes in Peru are equipped with networks of multiparameter instruments, with the seismic monitoring being the most widely implemented. In this report, we present the situation of volcanic monitoring in Peru, the monitoring networks, the techniques employed, as well as efforts to educate and inform the public and officials responsible for disaster risk management.